For the People: A Documentary History of the Struggle for Peace and Justice in the United States (In Factis Pax: Journal of Peace Education and Social Justice, 2018)
For the People: A Documentary History of the Struggle for Peace and Justice in the United States, edited by Charles F. Howlettt and Robbie Lieberman, Charlotte, NC, Information Age Publishing, 2009, 351 pp., US $39.09 (paperback), US $73.09 (hardcover), ISBN 978-1-60752-305-5 (paperback).